Peran Kepuasan Konsumen Sebagai Pemediasi Praktek Kualitas dan Kinerja Bisnis UMKM di Kota Banda Aceh - Nurbismi Nurbismi; Endra Gunawan (J-MAS (Jurnal Manajemen dan Sains), 2019)
The Purpose of this research is to determine the effect of quality practice on customer satisfaction and business performance of small and medium entreprises in Banda Aceh. In the research, customer satisfaction employeed as intervening variable between quality practice and business performance. The sample of the research are 50 owners of small and medium entreprises, and then model analysis operarationalized by  hierarchical linier methods. The research found that quality practice has a significant and positive effect on customer satisfaction and business performance. The existence of customer satisfaction can be an intervening variable between business performance and quality practice. The mediating effect showed by customer satisfaction is partial mediating.